2020
DOI: 10.5114/wo.2020.97607
|View full text |Cite
|
Sign up to set email alerts
|

Real-world treatment practice in patients with advanced melanoma

Abstract: Introduction The treatment outcomes of patients with advanced/metastatic melanoma were poor before the use of new therapeutic options. Material and methods A retrospective analysis was conducted among 287 patients with unresectable stage III and stage IV melanoma treated at the Maria Sklodowska-Curie National Research Institute of Oncology Cracow Branch, from 2013 to 2019. All enrolled patients were treated with immunotherapy (IT; consisting of pembrolizumab/nivolumab, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
(52 reference statements)
3
8
0
Order By: Relevance
“…This duration was based on mean second-line PFS data for patients previously treated with PD-1 therapies reported by Zimmer et al [ 33 ]. The median PFS from this study is broadly aligned with similar second-line PFS estimates from the literature based on real-world data [ 38 ]. Despite the limitations in our approach to estimating costs related to subsequent treatments, the economic evaluations presented here are generally consistent with the findings from a prior economic evaluation based on a treatment sequencing analysis, which demonstrated that first-line therapy with NIVO + IPI (followed by BRAF + MEK inhibitor therapy) was most cost effective at thresholds greater than $80,000 per QALY [ 32 ].…”
Section: Discussionsupporting
confidence: 77%
“…This duration was based on mean second-line PFS data for patients previously treated with PD-1 therapies reported by Zimmer et al [ 33 ]. The median PFS from this study is broadly aligned with similar second-line PFS estimates from the literature based on real-world data [ 38 ]. Despite the limitations in our approach to estimating costs related to subsequent treatments, the economic evaluations presented here are generally consistent with the findings from a prior economic evaluation based on a treatment sequencing analysis, which demonstrated that first-line therapy with NIVO + IPI (followed by BRAF + MEK inhibitor therapy) was most cost effective at thresholds greater than $80,000 per QALY [ 32 ].…”
Section: Discussionsupporting
confidence: 77%
“…Thus, the few available studies with real-world data showed positive achievements of targeted therapy for the cohort of BRAF-mutant melanoma patients. Moreover, our study of real-world clinical practice was the largest and included 2.5-fold more patients with BRAF-mutant advanced melanoma compared to those of the above-mentioned study (382 vs. 152 patients) and demonstrated increased median OS (22.6 months) and 2-year OS (47.2%) compared to the earlier reported study [ 30 ] in patients receiving the first-line targeted therapy. In addition, even though the patients included in the ADMIRE study had poorer prognostic factors, the data showed essentially higher effectiveness in a real-world setting, which may correspond to phase 3 clinical trials.…”
Section: Discussionmentioning
confidence: 83%
“…Median OS and PFS in the experimental group from the start of the first-line treatment were 14.9 and 6.7 months, respectively. The first-line treatment of patients involved IT, TT, or chemotherapy, and the median OS reached 19.2, 12.6, and 15.9 months, respectively [ 30 ]. Thus, the few available studies with real-world data showed positive achievements of targeted therapy for the cohort of BRAF-mutant melanoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Brain metastases were detected in 64 (22%) patients. The first-line treatment of patients involved immunotherapy, targeted therapy, or chemotherapy, and the median OS reached 19.2, 12.6, and 15.9 months, respectively [9]. In this analysis the unexpected finding was that the median OS for targeted therapy is lower than that in chemotherapy group.…”
Section: Discussionmentioning
confidence: 69%